Finite element analysis for thermal enhancement in power law hybrid nanofluid - Nazir, Umar; Sohail, Muhammad; Singh, Abha; Muhsen, Sami; Galal, Ahmed M.; Tag El Din, El Sayed M.; Hussain, Syed M. (Frontiers in Physics, 2022)
Ethylene glycol with nanoparticles behaves as a non-Newtonian fluid and its rheology can be best predicted by the power-law rheological approach. Further nanoparticles (molybdenum disulfide and silicon dioxide) are responsible for anti-oxidation, anti-evaporation, and anti-aging. Therefore, their dispersion in ethylene glycol is considered as these properties make the nanofluid stable. This article examines the impact of molybdenum disulfide and silicon dioxide on the thermal enhancement of ethylene glycol as it is a worldwide used coolant. Moreover, simultaneous effects of temperature and concentration gradients, Joule heating, viscous dissipation, thermal radiations, and buoyancy forces are modeled and developed, and investigations are computed by the finite element method. An increase in temperature due to the composition gradient and an increase in concentration due to the temperature gradient are observed. A significant increase in the Ohmic phenomenon with an increase in the intensity of the magnetic field is observed. Numerical experiments are performed by considering single-type nanoparticles (MoS2) and hybrid-type nanoparticles (simultaneous dispersion of SiO2 andMoS2is considered). During the visualization of simulations, the effective thermal conductivity of MoS2-SiO2-ethylene glycol is observed.